15-2(y-3)=6(2y+6)-5y

Simple and best practice solution for 15-2(y-3)=6(2y+6)-5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15-2(y-3)=6(2y+6)-5y equation:


Simplifying
15 + -2(y + -3) = 6(2y + 6) + -5y

Reorder the terms:
15 + -2(-3 + y) = 6(2y + 6) + -5y
15 + (-3 * -2 + y * -2) = 6(2y + 6) + -5y
15 + (6 + -2y) = 6(2y + 6) + -5y

Combine like terms: 15 + 6 = 21
21 + -2y = 6(2y + 6) + -5y

Reorder the terms:
21 + -2y = 6(6 + 2y) + -5y
21 + -2y = (6 * 6 + 2y * 6) + -5y
21 + -2y = (36 + 12y) + -5y

Combine like terms: 12y + -5y = 7y
21 + -2y = 36 + 7y

Solving
21 + -2y = 36 + 7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-7y' to each side of the equation.
21 + -2y + -7y = 36 + 7y + -7y

Combine like terms: -2y + -7y = -9y
21 + -9y = 36 + 7y + -7y

Combine like terms: 7y + -7y = 0
21 + -9y = 36 + 0
21 + -9y = 36

Add '-21' to each side of the equation.
21 + -21 + -9y = 36 + -21

Combine like terms: 21 + -21 = 0
0 + -9y = 36 + -21
-9y = 36 + -21

Combine like terms: 36 + -21 = 15
-9y = 15

Divide each side by '-9'.
y = -1.666666667

Simplifying
y = -1.666666667

See similar equations:

| 2-9(1-8a)=32 | | -9(10+6x)=3x-33 | | 6x-3=651 | | 0+1=2(5-3) | | 5(3x-1)-3(4x+5)=7 | | .5x+.75=2.3 | | Z-4/10=9 | | 15-3=2(x+3) | | 5x-7(4x+3)=94 | | 6=17-p | | x^(-2/5)=0 | | 3x+21=7x-1 | | 8=x/4-4 | | 1/3x=-21 | | 4x-(5-10x)= | | -3-2(2)=7 | | 2u-3=-15 | | 3/2-1/4y=1/2 | | 3c+2-2c-5=2-0.67c | | 3(4x+1)-5x= | | 12.99+1.75=35 | | 2log(-5.8x+1.5)+x+1=0 | | 6x=-8(x-7) | | -3x=4x+7(5+4x) | | 2z^2+6z-8=0 | | 0=-3(0)+2 | | 7r+7+8=-20 | | 5x+9y=10000 | | 3(w-3)-8w=16 | | N/5=65 | | 13=14g | | x=13-24 |

Equations solver categories